Prevalence of dual diagnosis in the south of Peru: descriptive clinical study - Jonathan A. Zegarra-Valdivia; Brenda Nadia Chino Vilca; Ernesto Cazorla Perez (Interacciones)
Comorbidity between substance use disorders and other psychiatric disorders or dual diagnosis (PD) is characterized by difficulty in their therapeutic approach, constant relapses and hospital admissions, as well as higher violent and criminal behavior. Our objective was to determine the prevalence of PD in individuals treated at a psychiatric center in Arequipa, Peru. It is a descriptive epidemiological study based on analysis of 445 case histories (HC) of patients admitted during the period of three years (2011-2013). Socio-demographic and clinical characteristics of subjects by comparing those who had a diagnosis of PD, with those who had a diagnosis just by consuming psychotropic substances were established. The results show a prevalence of dual diagnosis in 49%. The average ages were M = 31.45, DS = 15.59 in the with dual diagnosis group CPD and M = 33.93, DS = 15.48 in the without dual diagnosis group SPD; the prevalence of substance use was 51% SPD. Alcohol was the most used substance, followed by cannabis marijuana and cocaine base (PBC). The socio-family and individual vulnerability of the population is evidence for protection or resistance to mental illness, as well as the lack of implementation of effective policies in mental health care for dual disorders, showing worse prognosis and indexes every time higher.